Aggregation of atomically precise graphene nanoribbons. Issue 86 (27th November 2017) - Shekhirev, Mikhail; Vo, Timothy H.; Kunkel, Donna A.; Lipatov, Alexey; Enders, Axel; Sinitskii, Alexander
Abstract : Atomically precise chevron graphene nanoribbons can form bulk π–π stacked aggregates as well as few-μm-long one-dimensional structures on surfaces that could be used for electronic device fabrication. Abstract : Solution bottom-up approaches can be used to prepare bulk quantities of narrow atomically precise graphene nanoribbons (GNRs) with various widths and geometries. These GNRs are often considered as promising materials for electronic and optoelectronic applications. However, the handling and processing of nanoribbons for practical applications can be difficult because of their entanglement and aggregation, and thus poor solubility in conventional solvents. In this work, we studied the aggregation-dependent properties of solution-synthesized chevron GNRs in a variety of solvents. We demonstrate that the spectroscopic features observed in the experimentally measured absorbance spectra of chevron GNRs are in a good agreement with the theoretically predicted excitionic transitions. We also show that the absorbance spectra of GNRs evolve with aggregation time, which is important to consider for the spectroscopic determination of optical bandgaps of nanoribbons. We discuss two types of GNR assemblies: bulk aggregates of π–π stacked nanoribbons that form in a solution and rather long one-dimensional (1D) structures that were observed on a variety of surfaces, such as Au(111), mica and Si/SiO2 . We demonstrate that the few-μm-long 1D GNR structures can be conveniently visualized by conventional microscopy techniques and used for the fabrication of electronic devices.